The Effect of Academic Supervision, Teacher Compensation Through Work Motivation on The Performance of State Vocational High School Teachers in Landak District - Hendri, Pebrianus; Tawarik, Oxtapianus; Yonas, Apolonius (Institut of Shanti Bhuana, 2024)
The purpose of this study was to identify and analyze (1) the direct influence of academic supervision on teacher performance, (2) the direct influence of compensation on teacher performance, (3) the effect of work motivation on teacher performance, (4) the direct and indirect influence academic supervision of the teacher's performance through employee motivation, (5) the direct and indirect influence compensation of the teacher's performance through employee motivation. The type of research used is correlated with data collection tools using questionnaires, and the analysis techniques used are validity, reliability, regression analysis and path analysis. The results showed that Academic supervision on the performance of teachers by 0.308, or 30.8%, and motivation effect on teacher performance a contribution of 0.355, or 35.5%, and work motivation on teacher performance by 0.258, or 25.8%. Academic supervision has a direct or indirect effect on teacher performance. Indirect supervision of the performance of teachers through motivation is mediated with a contribution of 6.1528. Compensation directly or indirectly affects the performance of teachers through work motivation as mediation with a contribution of 3.2269.